Ultrafast exciton dynamics in ZnxCd1-xSe nanobelt. - Sulistio, Arief. (2013)
ZnxCd1-xSe nanobelts are interesting ternary alloy nanostructures with many unique properties suitable for lasing applications. Herein, we investigate the potential use of ZnxCd1-xSe nanobelt as a room-temperature gain medium for single photon and two photon pump lasing. Ultrafast femtosecond laser was used to probe the exciton dynamics in this material. The emission spectra shows a continuous shift of band edge emission from 460nm to 730nm which correspond to pure ZnSe and CdSe emission, indicating a formation of ternary alloy rather than mixed of independent binary phases. We also examined the pump power dependence of emission which exhibits a super linear relationship above certain pump threshold. This threshold increasing with high concentration of Cd in composition and jumps significantly around 650nm.